The Effect of Lithotomy Position on Nerve Stretch: A Cadaveric Study. Issue 6 (November 2017) - Deveneau, Nicolette E.; Forbis, Courtney; Lipetskaia, Lioudmilla; Kinman, Casey L.; Agrawal, Anubhav; Herring, Nicole R.; Francis, Sean L.
Abstract : Objective: The objective of our study was to design a method to measure nerve stretch in cadaveric subjects and then use the method to assess femoral nerve stretch in the lithotomy position with varying degrees of flexion and extension. Methods: A university-based, cadaveric observational study of femoral nerve stretch was conducted. In 6 cadaveric subjects, femoral nerve near the inguinal ligament was dissected in each cadaveric subject. The nerve was marked, and digital images of the nerve were obtained in the supine position and lithotomy position in both flexion and extension. Distances were calculated using the ratio of pixels to millimeter specific for each image. The average distance for each set of images was then used to calculate the percent change from supine for each position. Results: We were able to assess nerve stretch using photo-editing software. For extended position, all nerves showed some degree of stretch with the mean percent change in nerve length being 10.35%. For all other positions, most showed a decrease of nerve length. There was not a significant relation between degree of extension and stretch (Pearson r, P < 0.05). Conclusions: Hip extension between 10 and 20 degrees consistently stretches the femoral nerve greater than 5%. The potential for femoral nerve stretch and avoiding hip extension should be considered when positioning a patient in lithotomy for surgical procedures. Abstract : This study demonstrates the amount of femoral nerve stretch and relaxation that occurs in female cadavers in variations of the lithotomy position.